Synthesis, Characterization and Ammonia Sensing Studies on Novel Polypyrrole/Zinc Oxide/SWCNT Nanocomposite - Husain, Ahmad; Shariq, Mohd Urooj; Ahmad, Sharique; Ahmad, Anees; Mohammad, Faiz (Asian Journal of Chemistry, 2020)
Herein, the synthesis and characterization of a novel polypyrrole (PPy)/zinc oxide (ZnO)/SWCNT nanocomposite together with pristine polypyrrole is reported. These as-prepared materials have been characterized by FT-IR spectroscopy, X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and thermogravimetric analysis (TGA) techniques. The PPy/ZnO/SWCNT nanocomposite is used as a pellet-shaped ammonia sensor. The sensing response is calculated in terms of variation in the DC electrical conductivity at different concentration of ammonia ranging from 50 ppm to 2000 ppm. The sensing response of the sensor is determined at 2000, 1000, 500, 400, 300, 200, 100 and 50 ppm and found to be 76.3, 60.5, 54.8, 52.6, 50.2, 48.5, 40.5 and 36.6%, respectively The sensor displays excellent reversibility along with very high selectivity and stability. Finally, a sensing mechanism is also proposed involving polarons (charge carriers) of polypyrrole and lone pairs of electrons of ammonia molecules